Funding for change: New Zealand pharmacists' views on, and experiences of, the community pharmacy services agreement. (28th April 2016) - Kinsey, Hannah; Scahill, Shane; Bye, Lynne; Harrison, Jeff
Abstract: Objective: To explore pharmacist's views on the shift in ethos, funding and service delivery model introduced through the New Zealand's Community Pharmacy Services Agreement (CPSA). Methods: A purposive sampling approach drew pharmacists from a matrix who were then contacted via telephone and invited to be interviewed. Semistructured interviews were conducted face-to-face with community pharmacists ( n = 17) across urban and rural New Zealand. An interview schedule exploring 12 subject areas was used to facilitate discussion and determine pharmacist's views and understanding of the CPSA. The interviews were recorded and transcribed verbatim and a general inductive approach was taken to identifying emergent themes. Key findings: Key themes that emerged were: pharmacists supported the philosophy behind the CPSA, pharmacists understanding of the CPSA, implementing CPSA-related services, perceived impact on patient outcomes and future sustainability of the CPSA. Overall, pharmacists supported the alignment of funding with patient-centred services, but pharmacy owners reported difficulty understanding the funding model, resulting in uncertainty over income. Several pharmacists believed the quality of care offered had not changed, while others found their attitudes towards care had evolved. All pharmacists communicated an increase in their workload and many perceived the sustainability of the CPSA to be linked to its ability to financially sustain community pharmacies. Conclusions: The majority of pharmacists believed in the philosophy of the CPSA, but expressed concerns over funding, workload and benefits for patients. Future research is required to determine generalisability of these findings, investigate patient perspectives and assess the effect of the CPSA on patient outcomes.